8(2x+5)=3(x+4)+2

Simple and best practice solution for 8(2x+5)=3(x+4)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(2x+5)=3(x+4)+2 equation:


Simplifying
8(2x + 5) = 3(x + 4) + 2

Reorder the terms:
8(5 + 2x) = 3(x + 4) + 2
(5 * 8 + 2x * 8) = 3(x + 4) + 2
(40 + 16x) = 3(x + 4) + 2

Reorder the terms:
40 + 16x = 3(4 + x) + 2
40 + 16x = (4 * 3 + x * 3) + 2
40 + 16x = (12 + 3x) + 2

Reorder the terms:
40 + 16x = 12 + 2 + 3x

Combine like terms: 12 + 2 = 14
40 + 16x = 14 + 3x

Solving
40 + 16x = 14 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
40 + 16x + -3x = 14 + 3x + -3x

Combine like terms: 16x + -3x = 13x
40 + 13x = 14 + 3x + -3x

Combine like terms: 3x + -3x = 0
40 + 13x = 14 + 0
40 + 13x = 14

Add '-40' to each side of the equation.
40 + -40 + 13x = 14 + -40

Combine like terms: 40 + -40 = 0
0 + 13x = 14 + -40
13x = 14 + -40

Combine like terms: 14 + -40 = -26
13x = -26

Divide each side by '13'.
x = -2

Simplifying
x = -2

See similar equations:

| 7x-2(5-x)=3+2x+1 | | 5*12+13+3*14+2*15+4*16+17+19+3*20/20 | | 12-8m=2m+2 | | 14-(2q+5)=(-2q)+9 | | -3/4x+5/4=x+3 | | 12x+4/4(x-1)(x+1)=5/4 | | 8x-16=4(2x-4) | | 22=4+3t | | x+30=93 | | -1/4y+5/4=-5/6y+5/3 | | -42=14y | | .2x-3=1 | | -5(9r+10)+5r=10(r+10) | | 2.2x-3=1 | | 3r^2+10r-4=84 | | 9-3(9z+1)=-4(-z-6)-8 | | x^3-19x=-30 | | 15=5/9(f-32) | | -2y+20=-5y+5 | | 300-20x=150+20x | | 3.7+3.25x= | | 11x-31=90 | | 21-1/24(3x)=14-1/24(2x) | | 4x6/11 | | 8x+42=90 | | -n+8.5=14.4 | | -2+8(n-3)=2(-9n-5)+7 | | 2x^2-38x=0 | | 2x+5=10y | | 3u-14=-6u-5 | | (3h-1)(h+5)= | | 25x^2+10x-24=0 |

Equations solver categories